Lithocholic acid inhibits P2X2 and potentiates P2X4 receptor channel gating - Sivcev, Sonja; Slavikova, Barbora; Ivetic, Milorad; Knezu, Michal; Kudova, Eva; Zemkova, Hana (The Journal of steroid biochemistry and molecular biology, 2020)
The family of ATP-gated purinergic P2X receptors comprises seven bunits (P2X1-7) that are unevenly distributed in the central and peripheral nervous systems as well as other organs. Endogenous modulators of P2X receptors are phospholipids, steroids and neurosteroids. Here, we analyzed whether bile acids, which are natural products derived from cholesterol, affect P2X receptor activity. We examined the effects of primary and secondary bile acids and newly synthesized derivatives of lithocholic acid on agonist-induced responses in HEK293T cells expressing rat P2X2, P2X4 and P2X7 receptors. Electrophysiology revealed that low micromolar concentrations of lithocholic acid and its structural analog 4-dafachronic acid strongly inhibit ATP-stimulated P2X2 but potentiate P2X4 responses, whereas primary bile acids and other secondary bile acids exhibit no or reduced effects only at higher concentrations. Agonist-stimulated P2X7 responses are significantly potentiated by lithocholic acid at moderate concentrations. Structural modifications of lithocholic acid at positions C-3, C-5 or C-17 abolish both inhibitory and potentiation effects to varying degrees, and the 3α-hydroxy group contributes to the ability of the molecule to switch between potentiation and inhibition. Lithocholic acid allosterically modulates P2X2 and P2X4 receptor sensitivity to ATP, reduces the rate of P2X4 receptor desensitization and antagonizes the effect of ivermectin on P2X4 receptor deactivation. Alanine-scanning mutagenesis of the upper halve of P2X4 transmembrane domain-1 revealed that residues Phe48, Val43 and Tyr42 are important for potentiating effect of lithocholic acid, indicating that modulatory sites for lithocholic acid and ivermectin partly overlap. Lithocholic acid also inhibits ATP-evoked currents in pituitary gonadotrophs expressing native P2X2, and potentiates ATP currents in nonidentified pituitary cells expressing P2X4 receptors. These results indicate that lithocholic acid is a bioactive steroid that may help to further unveil the importance of the P2X2, and P2X4 receptors in many physiological processes.
Keywords: Neurons; Purinergic P2X Receptor Antagonists; Pituitary Gland, Anterior; Ion Channel Gating; ATP; kyselina lithocholová; HEK293 Cells; Purinergic P2X Receptor Agonists; purinergní receptory P2X2; Rats, Wistar; mužské pohlaví; Lithocholic Acid; Receptors, Purinergic P2X4; Receptors, Purinergic P2X7; purinergní receptory P2X4; Hypothalamus; hypothalamus; ženské pohlaví; Ivermectin; zvířata; HEK293 buňky; Humans; agonisté purinergního receptoru P2X; Purinergic P2X receptors; Allosteric modulation; neurony; Bile acids; purinergní receptory P2X7; gating iontového kanálu; potkani Wistar; Female; antagonisté purinergních receptorů P2X; Receptors, Purinergic P2X2; Lithocholic acid; lidé; Male; adenohypofýza; Animals